THE IMPACT OF FOOD ADDITIVES COMPLEX ON THE STRUCTURAL ORGANIZATION OF PULMONARY DIFFUSE LYMPHOID TISSUE SHOWN IN THE EXPERIMENT - Yeroshenko, G.A.; Donets, I.M.; Shevchenko, K.V.; Riabushko, O.B.; Zviaholska, I.M.; Onipko, V.V.; Peredera, R.V. (World of Medicine and Biology, 2023)
The paper presents the findings of morphometric and morphological studies of the diffuse lymphoid tissue of rat lungs under the combined effect of the food additives. It has been found that the condition of the diffuse lymphoid tissue of rat lungs, under the impact of the complex of food additives comprise of monosodium glutamate, sodium nitrite and Ponceau 4R, reflects the reaction of elements of the local defense barrier to the action of the components of the food additives’ complex, primarily functioning as antigens. This is manifested by the activation of processes of antigen-dependent differentiation of cells of the lymphoid lineage, undulating changes in the morphometric parameters and the degree of vascularization of the diffuse lung tissue.